Feeding problem as the risk factors for stunting among under five children in Kuantan – a case control study - Musa, Noraini; Kamaruzaman, Nor Azam; Pasi, Hafizah; Osman, Iskandar Firzada (2022)
Feeding problem in under five children may lead to negative sequelae particularly stunting which is the most prevalent form of malnutrition in this age group. This case control study aim to explore feeding problems as the risk factors for stunting among infants and young children in district of Kuantan, Pahang. A total of 40 children aged 6 to 59 months diagnosed with stunting and 120 children with normal height-for-age were included in the study with a ratio of 1 case: 3 control. Data were collected using an interviewer-guided questionnaire and a validated ATUCU5 (Approach to Unwell Children Under 5) feeding assessment checklist.